Multilocus genotyping of Giardia intestinalis in pet dogs of Medellín Colombia (2021)
According to a few parasitological and epidemiological studies, Giardia is the most prevalent parasitic infection among pet dogs in the city of Medellín, the second-largest city in Colombia. This study determined the assemblages of Giardia in the fecal samples of dogs obtained from 18 veterinary centers of Medellín. One hundred fecal samples of dogs diagnosed with Giardia using microscopy were analyzed via nested polymerase chain reaction (PCR) using three genes (gdh, bg, and tpi). The PCR products were purified and sequenced, and phylogenetic analyses were conducted using the maximum likelihood algorithm of the three loci. From the 100 samples analyzed, 47 were Giardia-positive via PCR. Genotypes C and D were detected in six samples, neither of which were associated with human infection. However, the zoonotic potential of Giardia cannot be ruled out because of the small number of samples that could be sequenced for assemblage assignation.